Ozone treatment of meat and meat products: a review - Gimenez, Maria Belen (2024)
Ozone treatment is a non-thermal method for disinfection; ozone is apowerful oxidizing agent that has been shown to be effective in reducingmicrobial load, extending the shelf life of meat products. This mini-reviewcovers the analysis of the antimicrobial ozone activity in different meats (beef,poultry, pork, seafood, etc.), emphasizing the ozone application methods(liquid or gaseous phase), the applied concentrations and contact times andthe effects of ozone treatment onmeat quality, safety, and sensory properties.It has been demonstrated that ozone is effective against a broad range ofmicroorganisms, including both Gram-positive and Gram-negative bacteria,spores, and vegetative cells. The efficacy of ozone depends on various factors,such as concentration, type of treatment, temperature, and presence oforganic material. Ozone treatment, known for its rapid decomposition andlack of residue, provides an environmentally friendly alternative to traditionalchemical sanitizers. Ozone treatments exhibit promising results in enhancingthe safety and extending the shelf life of meat products. According to thefindings, the application of ozone is an effective technology for prolonging theshelf life of different types of meats and meat products, requiring carefulestablishment of conditions on a case-by-case basis.